2022
DOI: 10.1155/2022/7368691
|View full text |Cite
|
Sign up to set email alerts
|

Using IoT Protocols in Real-Time Systems: Protocol Analysis and Evaluation of Data Transmission Characteristics

Abstract: In the Internet of things, many data transfer protocols are used for various tasks. In this article, we consider the application layer protocols that are the main ones for transmitting messages in the IoT. The main problems are unpredictability, lack of stability of data transmission delays, and non-determinism, which are also important for real-time systems. The purpose of this study is to determine the most appropriate middleware and data transfer protocol for systems with high data transfer requirements, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Using a mathematical method, throughput parameters on different stream loss rates and the effect of the frame sizes were examined. Gavrilov et al (2022) analyzed MQTT, Real Time Publish Subscribe protocol (RTPS, an interoperability protocol for DDS implementations), Java Message Service (JMS), and AMQP protocols to find out what tasks these protocols should be used for and whether they can be used in robotic and autonomous systems where high data transmission requirements are imposed. They concluded that RTPS is the best solution for real-time systems with different traffic and that MQTT performs well when transmitting short messages.…”
mentioning
confidence: 99%
“…Using a mathematical method, throughput parameters on different stream loss rates and the effect of the frame sizes were examined. Gavrilov et al (2022) analyzed MQTT, Real Time Publish Subscribe protocol (RTPS, an interoperability protocol for DDS implementations), Java Message Service (JMS), and AMQP protocols to find out what tasks these protocols should be used for and whether they can be used in robotic and autonomous systems where high data transmission requirements are imposed. They concluded that RTPS is the best solution for real-time systems with different traffic and that MQTT performs well when transmitting short messages.…”
mentioning
confidence: 99%